Examining English as a Foreign Language teachers’ Technological Pedagogical Content Knowledge framework in higher education in Guizhou, China - Yang, Mingxing; Jeyaraj, Joanna Joseph; Ahmad, Norhakimah Khaiessa; Yang, Wei (Springer Science and Business Media B.V., 2026)
The technological pedagogical and content knowledge (TPACK) framework has seven distinct factors, having been empirically validated across multiple studies. Furthermore, the effects of demographic factors such as gender and age on TPACK remain ambiguous. This study investigates EFL teachers’ TPACK (EFL-TPACK) framework in higher education in Guizhou, China. The objectives were to verify the validity of the seven factors of the EFL-TPACK framework, to assess the EFL-TPACK level of EFL teachers, and to explore the correlations between demographic factors and the EFL-TPACK framework. Data were collected from 286 EFL teachers across various institutions and universities in Guizhou using the adapted EFL-TPACK questionnaire. Noteworthy findings include the following: (a) the seven-factor EFL-TPACK framework was supported with acceptable fit in Guizhou, China, (b) the EFL-TPACK of EFL teachers in higher education in Guizhou was moderate level; (c) there was a correlation between demographic factors and EFL-TPACK framework; and (d) EFL teachers’ majors and professional titles in Guizhou were irrelevant to EFL-TPACK framework. Hence, this research suggests that policymakers or course developers should take more demographic factors into consideration when designing professional development programs.